Media Pembelajaran IPS yang Inovatif - Rokaliana Rokaliana (Proceedings Series on Social Sciences & Humanities, 2022)
In this all-digital era, education in Indonesia is increasingly facing massive challenges in achieving educational goals. Among the many options for developing existing learning components, the learning media has a high creative power. Because the learning media contains elements to facilitate/help the learning process, the results of the application of the media can be seen directly. The purpose of this research is to find out the innovative social studies learning media. From the results of the study, there are five steps to determine learning media, namely designing learning media, determining the media to be selected, designing learning media innovations, starting to make learning media, applying media in the learning process.